Development of muffin with the incorporation of olive pomace flour, extra virgin olive oil and hydrolyzed soy protein (Research, Society and Development, 2022)
Olive pomace flour, extra virgin olive oil and hydrolyzed soy protein are ingredients rich in compounds with beneficial health properties, such as phenolic compounds, dietary fiber, amino acids and fatty acids. In this sense, the present study aimed to evaluate the influence of partial replacement of wheat flour, hydrogenated vegetable fat and sucrose by olive pomace flour, extra virgin olive oil and hydrolyzed soy protein, respectively, in muffin-type cakes. The determination of the ideal formulation with the alternative ingredients was carried out through the Response Surface Methodology, exploring a Simplex-Centroid Mixture Design using physicochemical parameters as dependent variables. The optimum point was obtained using 38.00 % olive pomace flour, 3.75 % extra virgin olive oil, and 4.05 % hydrolyzed soy protein. In general, it was observed that the alternative ingredients had positive effects on the texture profile of the muffins and provided products with darker shades, characteristics of the ingredients used. Nutritionally, an increase in total dietary fiber, ash and lipid content was observed. In contrast, the starch content decreased, but the total caloric value was similar between the standard sample and the optimum. Therefore, the partial replacement of ingredients demonstrated feasibility and potential for bakery goods.